2019
DOI: 10.2478/aoas-2019-0057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Caponisation on Bone Development in Native Male Chickens

Abstract: The aim of the study was to determine the effect of caponisation on the morphometric traits and mechanical parameters of tibial and femoral bones in Greenleg Partridge cocks. The experiment involved 200 cocks. At the age of 8 weeks, 100 birds were subjected to surgical castration. At week 24, the birds were slaughtered and tibial and femoral bones were collected from 10 non-caponised cocks and 10 capons. The caponisation surgery had no effect on the weight and length of any of the long bones but resulted in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
16
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(41 citation statements)
references
References 48 publications
22
16
3
Order By: Relevance
“…This result is in accordance with similar studies [35,44,53]. In the conducted research, it was noted that castration did not in uence the tibia length in all analyzed rearing period groups of animals, which is consistent with other studies [7,20,30,31,54]. Varied results also apply to the bone mass.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This result is in accordance with similar studies [35,44,53]. In the conducted research, it was noted that castration did not in uence the tibia length in all analyzed rearing period groups of animals, which is consistent with other studies [7,20,30,31,54]. Varied results also apply to the bone mass.…”
Section: Discussionsupporting
confidence: 92%
“…A similar reduction in bone mass of tibia bone among capons, compared to cockerels was shown by Zawacka et al [44], but only among individuals slaughtered at 24 weeks of age, whereas in the case of 12-week-old animals authors found no such effect. However, similarly to the presented study, other studies report that caponization has no signi cant effect on tibia and femur bone mass [14,30,31,52,54,55].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations